Linc00511 Knockdown Inhibited TGF-β1-Induced Epithelial–Mesenchymal Transition of Bronchial Epithelial Cells by Targeting miR-16-5p/Smad3. Issue 3 (May 2023) - She, Weiwei; Sun, Tianshou; Long, Chengfeng; Chen, Meiyu; Chen, Xu; Liao, Qinxue; Wang, Mingdong
Background: Airway remodeling in patients with asthma was correlated with induced epithelial– mesenchymal transition (EMT) of bronchial epithelial cells. Objective: This study examined the mechanism of Linc00511 on induced EMT of bronchial epithelial cells after transforming growth factor-β1 (TGF-β1) induction. Methods: The human bronchial epithelial cell 16HBE was treated with 10 ng/mL TGF-β1 for 12 h, 24 h, or 48 h to induce EMT. Cell proliferation and migration rate were detected using CCK8 and wound healing assays, respectively. The expression of key markers of EMT (E-cadherin, N-cadherin, Small mothers against decapentaplegic family member 3 [Smad3], and slug) was tested by Western blot. Results: We found that Linc00511 was time dependently increased in TGF-β-treated 16HBE cells. Silencing Linc00511 reduced 16HBE cell proliferation, migration, and EMT progress. In addition, the dual-luciferase reporter assay showed Linc00511 was a molecular sponge for miR-16-5p. MiR-16-5p decreased the expression of Smad3 by targeting its 3′-untranslated region (3′UTR). After TGF-β1 exposure, miR-16-5p silencing counteracted the decreases of 16HBE cell proliferation, migration, and EMT induced by Linc00511 knockdown. And Smad3 overexpression also reversed the inhibitory effect of Linc00511 knockdown on proliferation, migration, and EMT progression in TGF-β1-induced human bronchial epithelial cells. Conclusion: Linc00511 may be a valuable biomarker for asthma therapy.